COMMUNITY EMPOWERING UNTUK PENINGKATAN PEREKONOMIAN DAN PEMBERDAYAAN PEREMPUAN MELALUI UMKM PT PLN (PERSERO) UIT JBB DI KOTA DEPOK - Dewi, Meylinda Kumala; Yuliani, Magvira; Praptiningsih, Novi Andayani (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2025)
This article describes the formation of organizational communication of PT PLN UIT JBB to make a Srikandi program that is the result of the alignment of Community Empowering and Social and Environmental Responsibility (TJSL). This shows the participation of women in achieving the performance of a company. Of course this encourages the involvement of women in the issues to be studied because it illustrates the role and gender equality in a company and organization. This study aims to identify how Community Empowering PT PLN (Persero) UIT JBB empowers women through the UMKM program in Depok City and the impacts arising from the UMKM program on the economy of women in Depok City. This study uses the ACTORS theory by Cook & Macaulay as a concept for the implementation of Community Empowering and Corporate Social Responsibility (CSR). The approach used in this study is a qualitative descriptive approach with a case study method and thematic data analysis. In collecting data, this study uses in-depth interview techniques, observation, and documentation. The subjects in this study were Mrs. Dhini as the TJSL Division of PT PLN (Persero) UIT JBB and Single Parents. The results of the study illustrate that MSMEs run through PT PLN's Community Empowering are able to become an effort for women to improve the economy and end marginalization of women, especially in the realm of work.